COGNITIVE-BEHAVIORAL THERAPY TECHNIQUES AS A TOOL FOR SUPPORTING THE PSYCHOLOGICAL RESILIENCE OF FUTURE PSYCHOLOGISTS (Psychology Travelogs, 2025)
The article is devoted to the problem of psychological resilience of future psychologists and the search for effective tools for its support and development. Psychological resilience of future psychologists is considered as a complex systemic formation that includes abilities, skills, and the ability to find and apply one's own adaptive resources to maintain functionality, constructively respond, and recover in the face of external challenges. Psychological resilience as a personal resource is formed through the development of emotional regulation strategies, cognitive flexibility, correction of destructive thought patterns, and adaptive behavior, which are the main elements of the cognitive-behavioral approach. Cognitive-behavioral therapy is considered one of the most effective tools for supporting and developing psychological resilience in future psychologists.The results of an empirical study of the manifestation and analysis of the components of psychological resilience of future psychologists using the Skala Pomiaru Prężności – SPP-25 N. Oginska-Bulik, Z. Yuchinsky are described. The results of the diagnostics of psychological resilience and its components in future psychologists at different training courses are analyzed. To study the cognitive component of psychological resilience, the Post-Traumatic Cognition Inventory (PCTI) by E.B. Foa, A. Ehlers, D.M. Clark, D.F. Tolin, S.M. Orsillo was used. A comparative analysis of the features of the manifestation of the cognitive component of future psychologists with different levels of psychological resilience was conducted.The results obtained helped to outline the general directions of work using cognitive-behavioral therapy and to identify weak links in the mechanisms and components of psychological resilience of future psychologists. A training program and cognitive-behavioral therapy techniques are described to support and develop psychological resilience of future psychologists.
Keywords: psychological stability; resilience; cognitive sphere; cognitive behavioral therapy techniques; future psychologists